AESTHETIC IDEAS IN UKRAINIAN AND BRITISH PHILOSOPHY OF 17-18TH CENTURIES - Viktoriya Havrylenko (International Journal of Innovative Technologies in Social Science, 2020)
Understanding of beauty is one of the valid exponents of the individual worldview. And aesthetics ideas express a worldview of the historical and cultural age. Why is the world beautiful? What is the beauty of the Universe, nature, and human proves? Those issues troubled both Ukrainian and British philosophers of the 17-18 centuries. In this article, I outline and compare philosophical views of aesthetics of Vitaliy from Dubno, Kyrylo Tranquilion- Stavrovetsky, Theophan Prokopovych, Heorhiyi Konysky, John Locke, George Berkeley, Francis Hutcheson, and David Hume. The aesthetics ideas of these philosophers are in many common. They regard the Universe and the person in terms of beauty and divinity. Humanistic tendencies of the era expressed in recognition of the perfectness and beauty of the human. On the whole, the ideas of philosophers sound like peculiar Aesthetical Optimism. Because, even ugliness is not excessive, and enhances the beauty and perfection of the Universe.